The Response of the International Community to the Genocide in Rwanda and the War in Ukraine - Maksymiuk, Magdalena (Review of European and Comparative Law, 2023)
The present thesis aims to describe the response of the international community to the genocide in Rwanda, and to assess current actions in the context of the war in Ukraine. It defines what genocide is, how it happened in Rwanda, and what proves that the incidents in Ukraine can be referred to as genocide.